Cognitive development following ART: effect of choice of comparison group, confounding and mediating factors. - Carson, C; Kurinczuk, J; Sacker, A; Kelly, Y; Klemetti, R; Redshaw, M; Quigley, M (Oxford University Press, 2010)
BACKGROUND: Epidemiological studies have examined the health of children born after assisted reproductive technology (ART), with contradictory results. In this article, we address the question 'Do singletons born after ART have a poorer cognitive developmental outcome at 3 years of age?' We assess the implications of using different comparison groups, and discuss appropriate analytical approaches for the control of confounding and mediating variables. METHODS: Data were drawn from the Millennium Cohort Study. Interviews captured sociodemographic, behavioural and pregnancy information. Developmental assessments conducted at age three included the British Ability Scales II Naming Vocabulary (BAS-NV) instrument. We compared ART infants (born after IVF or ICSI) to four comparison groups: a 'matched' group; a 'subfertile' group (time to conception >12 months); a 'fertile' group (time to conception <12 months); and an 'any spontaneous conceptions' group. Linear regression provided estimates of the difference in mean BAS-NV scores in the ART and comparison groups; both unadjusted estimates and those adjusted for confounding and mediating factors are presented. RESULTS: In the unadjusted analyses, ART children gained significantly better BAS-NV test results than did the comparison group children. When converted to an estimate of developmental age gap, ART children were 2.5, 2.7, 3.6 and 4.5 months ahead of the 'matched', 'subfertile', 'fertile' and 'spontaneous conception' children, respectively. After adjusting for confounding and mediating factors, the differences were reduced, and were not statistically significant. CONCLUSIONS: ART is not associated with poorer cognitive development at 3 years. We have highlighted methodological considerations for researchers planning to study the effect of infertility and ART on childhood outcomes.